THE INFLUENCE OF ORGANIZATION CULTURE AND WORK MOTIVATION TOWARD THE EMPLOYEE PERFORMANCE - Sari Laelatul Qodriah, Anne Lasminingrat, PuspaDewi Yulianty (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research is composed to find out organization culture, work motivation and employee performance and influence organization culture and work motivation toward the employee performance. This research is conducted for some matters: carrier ladder system not run optimally, compensation system and application of reward and punishment have not been appropriate enough, employee discipline level lower (Maseleno et al., 2019), the leadership has not supported and the work environment has not been in conducive situation yet.It is descriptive and verificative research. It purposes to obtain description about the status of phenomenon condition, and the variable characteristic, and to test the research hypothesis. Interview,questionnaire sheet and observation as empirical study.The research sample is taken by using probability sampling with stratified random sampling as the technique, where the population as parameter in this research is the amount of the employee. The number of population for the research is 142 and the sample is 75.From the research can be concluded that the organization culture happens in the company has not accustomed comprehensively and lower the employee work motivation, based on the statistical examination result, organization culture which directly determined the changes of employee performance is 15,4% and the one which dealt with work motivation is 7,0% so that the total influence is 22,4%. Beside that the power of work motivation directly determined that changes of employee performance is 7,7% and the one passes through its connection with organization culture is 7,0% so the total influence is 14,2%. The recommendation to repair the lack in organization culture, work motivation and employee performance such as defend of organization culture characteristic value all right indicate and make efforts for development of individual initiative, adjustment of compensation system and increase of courageos and released for extend, critical and a good idea. Beside that the management should comprehend and andfulfil the necessity particularly the basic requirements of the employees, and determine policy so it can conducive situation and increase their work performance.